Menyeimbangkan Transformasi Hijau dan Pertumbuhan: Implementasi Pajak Lingkungan dalam Konteks Asia – Studi Kasus Vietnam, Tiongkok, dan Malaysia - Tusta Prasidya; Wirawan Suhaedi; M. Ali Fikri; Intan Rakhmawati (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2025)
The case studies of environmental tax reforms in Vietnam, China, and Malaysia provide a comprehensive view of the challenges and opportunities faced by developing nations in implementing environmental fiscal policies to foster green growth. Each of these countries has adopted distinct approaches to environmental taxation, tailored to their specific economic, social, and environmental contexts. Vietnam and Malaysia have focused on targeted sectors such as fuel consumption and natural resource extraction, aiming to curb pollution and over-exploitation while generating revenue for sustainable initiatives. In contrast, China has taken a broader and more integrated approach by establishing a nationwide environmental tax system, complemented by the implementation of an Emissions Trading System (ETS), which seeks to reduce industrial emissions through market-based mechanisms. These case studies highlight several critical lessons that can inform future environmental fiscal reforms. One key takeaway is the importance of comprehensive tax coverage that addresses multiple sources of environmental degradation rather than focusing narrowly on a single sector. Additionally, strong enforcement mechanisms are essential to ensure compliance, as lax regulation or weak penalties can undermine the effectiveness of these taxes. Equally important is the strategic allocation of tax revenues, which should be directed towards sustainability projects such as renewable energy development, pollution control, and environmental restoration efforts. This revenue reinvestment can further bolster green growth and ensure long-term environmental benefits.